PELATIHAN CANVA UNTUK MENINGKATKAN SOFT SKILL MELALUI DESAIN E-KOMIK EDUKATIF - Muhlis Tahir; Setyaning Puji Kinanti; Nia Maulidya; Muhammad Roiqan Alfisani; Hengki Ulman Armanda Putra; Widya Ayu Zulaicha; Raja Gafira Wirdana Zain (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
The Canva training conducted at SMAN 2 Bangkalan aimed to enhance students’ soft skills through the creation of educational E-Comics. This program was based on the growing importance of soft skills—such as creativity, communication, and collaboration—in preparing students for the demands of the digital era. Despite high internet penetration among students, digital literacy, particularly in using creative applications, remains relatively low. The training was carried out luring with 34 participants and focused on understanding Canva’s features as well as hands-on practice in designing E-Comics on the theme of bullying. The results show that students successfully produced visually appealing and educational digital comics. In addition to improving graphic design abilities, the activity also strengthened critical thinking, visual communication, and moral awareness. Overall, the training proved effective in developing students’ creativity and digital competence.